The climate of Carpathian Region in the 20th century based on the original and modified Holdridge life zone system - Szelepcsényi Zoltán (CENTRAL EUROPEAN JOURNAL OF GEOSCIENCES, 2014)
The Holdridge life zone system has already been used a number of times for analysing the effects of climate change on vegetation. But a criticism against the method was formulated that it cannot interpret the ecotones (e.g. forest steppe). Thus, in this paper transitional life zones were also determined in the model. Then, both the original and modified life zone systems were applied for the climatic fields of database CRU TS 1.2. Life zone maps were defined in the Carpathian Region (43.5-50.5 degrees N, 15.5-28 degrees E) for each of five 20-year periods between 1901 and 2000. We estimated correctness of the result maps with another vegetation map using Cohen's Kappa statistic. Finally, temporal changes in horizontal and vertical distribution of life zones were investigated. The coverage of boreal region decreased with 59.46% during the last century, while the warm temperate region became almost two and a half larger (257.36%). The mean centres of those life zones, which were not related to mountains, shifted northward during the investigation period. In case of the most abundant life zone types, the average distribution elevation increased. Using the modified model, the potential distribution of forest steppe could be also identified.